2021
DOI: 10.2147/oajc.s291749
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Factors Associated with Immediate Postpartum Intrauterine Contraceptive Device Use Among Women Who Gave Birth at Government Hospitals of Gamo Zone, Southern Ethiopia, 2019

Abstract: Background: An intrauterine contraceptive device is suitable for women of all reproductive age groups for preventing unwanted pregnancies. Immediate postpartum family planning (PPFP) services need to be emphasized when the woman leaves the hospital. Despite the accepted demand for PPFP, many women do not access the services. Therefore, this study aimed to assess acceptability and factors associated with immediate postpartum intrauterine contraceptive device use among women who gave birth at government hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
4
8
0
Order By: Relevance
“…However, the association between PPIUCD use and maternal age requires cautious interpretation as the women were undersampled, hence the conclusion should be limited. Relatedly, we found women with at least three children (multiparty) are more likely to use PPIUCD, which is consistent with the findings of previous studies conducted in Rwanda, 19,20 Ethiopia, 21,22 Nigeria 16 and elsewhere 23 . Both findings might be explained by a need to limit the number of children among women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the association between PPIUCD use and maternal age requires cautious interpretation as the women were undersampled, hence the conclusion should be limited. Relatedly, we found women with at least three children (multiparty) are more likely to use PPIUCD, which is consistent with the findings of previous studies conducted in Rwanda, 19,20 Ethiopia, 21,22 Nigeria 16 and elsewhere 23 . Both findings might be explained by a need to limit the number of children among women.…”
Section: Discussionsupporting
confidence: 92%
“…Relatedly, we found women with at least three children (multiparty) are more likely to use PPIUCD, which is consistent with the findings of previous studies conducted in Rwanda, 19,20 Ethiopia, 21,22 Nigeria 16 and elsewhere. 23 Both findings might be explained by a need to limit the number of children among women.…”
Section: Discussionmentioning
confidence: 99%
“…The most common reasons for PPIUCD acceptance that emerged in our study align with the existing literature [ 16 , 24 , 31 33 ]. Immediate postpartum period is the appropriate time to begin contraception as women are highly motivated and not known to be pregnant.…”
Section: Discussionsupporting
confidence: 87%
“…There is no need for additional hospital visits for insertion, which also has the advantage of being convenient for both women and health care providers. We observed that the most common reasons for declining PPIUCD were resistance from the family members, notably the husband, insufficient knowledge about PPIUCD, preference for other less invasive methods of contraception, and fear of side effects, similar to other studies [ 16 , 24 , 31 33 ]. Nigam A et al have also pinpointed ineffective counseling as a crucial factor for refusal [ 34 ].…”
Section: Discussionsupporting
confidence: 86%
“…[30] The most common reasons for PPIUCD acceptance that emerged in our study align with the existing literature. [16,24,[31][32][33] Immediate postpartum period is the appropriate time to begin contraception as women are highly motivated and not known to be pregnant at this time. There is no need for additional hospital visits for insertion, which also has the advantage of being convenient for both women and health care providers.…”
Section: Discussionmentioning
confidence: 99%